Problematizing profit and profitability: discussions. Issue 4 (27th April 2020) - Lowe, Alan; Nama, Yesh; Bryer, Alice; Chabrak, Nihel; Dambrin, Claire; Jeacle, Ingrid; Lind, Johnny; Lorino, Philippe; Robson, Keith; Bottausci, Chiara; Spence, Crawford; Carter, Chris; et al.
Abstract : Purpose: The purpose of this paper is to report the outcome of an interdisciplinary discussion on the concepts of profit and profitability and various ways in which we could potentially problematize these concepts. It is our hope that a much greater attention or reconsideration of the problematization of profit and related accounting numbers will be fostered in part by the exchanges we include here. Design/methodology/approach: This paper adopts an interdisciplinary discussion approach and brings into conversation ideas and views of several scholars on problematizing profit and profitability in various contexts and explores potential implications of such problematization. Findings: Profit and profitability measures make invisible the collective endeavour of people who work hard (backstage) to achieve a desired profit level for a division and/or an organization. Profit tends to preclude the social process of debate around contradictions among the ends and means of collective activity. An inherent message that we can discern from our contributors is the typical failure of managers to appreciate the value of critical theory and interpretive research for them. Practitioners and positivist researchers seem to be so influenced by neo-liberal economic ideas that organizations are distrusted and at times reviled in their attachment to profit. Research limitations/implications: Problematizing opens-up the potential for interesting and significant theoretical insights. A much greater pragmatic and theoretical reconsideration of profit and profitability will be fostered by the exchanges we include here. Originality/value: In setting out a future research agenda, this paper fosters theoretical and methodological pluralism in the research community focussing on problematizing profit and profitability in various settings. The discussion perspectives offered in this paper provides not only a basis for further research in this critical area of discourse and regulation on the role and status of profit and profitability but also emancipatory potential for practitioners (to be reflective of their practices and their undesired consequences of such practices) whose overarching focus is on these accounting numbers.